2018
DOI: 10.1007/s12274-018-2019-7
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Metamaterial-based graphene thermal emitter

Abstract: The article Metamaterial-based graphene thermal emitter, written by Cheng Shi, Nathan H. Mahlmeister, Isaac J. Luxmoore, and Geoffrey R. Nash, was originally published electronically on the publisher’s internet portal (currently SpringerLink) on December 6th 2017 without open access. With the author(s)’ decision to opt for Open Choice the copyright of the article changed in February 2018 to © The Author(s) 2018 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…16 There are a lot of state-of-the-art works on designing of perfect thermal emitters. Shi et al 17 realized a broadband thermal emission with average emittance that is more than 70% by using a hexagonal boron nitride encapsulated graphene filament. Lenert et al 18 reported a high-efficiency solar thermophotovoltaic device coupling with a one-dimensional Si/SiO 2 emitter with a thermal efficiency of ∼75%.…”
Section: Introductionmentioning
confidence: 99%
“…16 There are a lot of state-of-the-art works on designing of perfect thermal emitters. Shi et al 17 realized a broadband thermal emission with average emittance that is more than 70% by using a hexagonal boron nitride encapsulated graphene filament. Lenert et al 18 reported a high-efficiency solar thermophotovoltaic device coupling with a one-dimensional Si/SiO 2 emitter with a thermal efficiency of ∼75%.…”
Section: Introductionmentioning
confidence: 99%